Аccounting and methodological aspects of capital expenditure for land improvement - J.P. Melnychuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article highlights the process of reflection in accounting the capital costs for land improvement. The main legislation governing this issue is covered. Also the article has agreed the key issues that ensure in accounting for capital expenditures for farmland improving. The survey has benefited such general scientific methods as: induction and deduction, dialectic, historical and systematic methods and specific methods of accounting. Due to the land reform the ownership of the land was changed. Lands which were owned by farms have been privatized and have received a particular owner. Now privatized lands constitute a significant part of farmland. The land managers require quality accounting information about composition and state of the land and improvements that occur to make an effective management. The numerous changes in legislation generate controversies in their interpretation and, consequently, it results in appearance of the discrepancies in the conduct of cost accounting for capital land improvement which will effect on the amount of net profit in future. The article reflects the economic substance of the process and fundamentally describes the implementation method of accounting for capital expenditure for land in accordance with the applicable law.